2020
DOI: 10.1007/s11120-020-00723-0
|View full text |Cite
|
Sign up to set email alerts
|

Modelling excitation energy transfer and trapping in the filamentous cyanobacterium Anabaena variabilis PCC 7120

Abstract: The phycobilisome (PBS) serves as the major light-harvesting system, funnelling excitation energy to both photosystems (PS) in cyanobacteria and red algae. The picosecond kinetics involving the excitation energy transfer has been studied within the isolated systems and intact filaments of the cyanobacterium Anabaena variabilis PCC 7120. A target model is proposed which resolves the dynamics of the different chromophore groups. The energy transfer rate of 8.5 ± 1.0/ns from the rod to the core is the rate-limiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Compartmental modeling analysis of picosecond time-resolved fluorescence studies revealed that, in intact cyanobacterial cells, the excitation energy from PBS can be rapidly distributed to the PSs ( Tian et al, 2011 ; Acuña et al, 2018 ). The varying architecture and the composition of PBSs among cyanobacterial species seem to hardly affect the energy funneling from the PBSs to the PSs ( Tian et al, 2011 ; Acuña et al, 2018 ; Akhtar et al, 2020 ; Biswas et al, 2020 ).…”
Section: Natural Diversity Of Ps Supercomplexesmentioning
confidence: 99%
“…Compartmental modeling analysis of picosecond time-resolved fluorescence studies revealed that, in intact cyanobacterial cells, the excitation energy from PBS can be rapidly distributed to the PSs ( Tian et al, 2011 ; Acuña et al, 2018 ). The varying architecture and the composition of PBSs among cyanobacterial species seem to hardly affect the energy funneling from the PBSs to the PSs ( Tian et al, 2011 ; Acuña et al, 2018 ; Akhtar et al, 2020 ; Biswas et al, 2020 ).…”
Section: Natural Diversity Of Ps Supercomplexesmentioning
confidence: 99%
“…Picosecond time-resolved measurements were carried out using a synchroscan streak-camera setup described elsewhere ( van Stokkum et al., 2008 ; Acuña et al., 2018 ; Biswas et al., 2020 ). Briefly, the femtosecond laser source, Coherent Vitesse Duo, pumped the regenerative Coherent RegA 900, and the output from the RegA further fed into the optical parametric amplifier Coherent OPA 9400, which had an output wavelength range from 470 to 770 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Mullineaux ( Mullineaux, 1994 ) reported that, at 77K, PSII-deficient Synechocystis cells exhibit a quantum efficiency of around 80% for PBS-to-PSI EET, contrasting with the 40% observed in wild-type (WT) cells. Conversely, room temperature picosecond studies, combined with functional kinetic modeling of experimental data, estimated a 50% EET to PSI within a PB-PSII-PSI megacomplex ( Tian et al., 2011 ; Biswas et al., 2020 ). In Synechococcus elongatus sp.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 PBS is found on the thylakoid membrane in red algae cyanobacteria. 29,30 The unique properties of PBS have some advantages in light harvesting, e.g., broadband absorption, fast and efficient energy transfer, angular robustness, and amplification of light concentration. 31 The structural organization of PBS can be classified into several categories such as hemidiscoidal, hemiellipsoidal, bundle-shaped, and block-shaped.…”
Section: Introductionmentioning
confidence: 99%
“…One of the natural organisms that utilize the antenna system as a light concentrator is cyanobacteria, and they have perfected their absorption mechanism through an evolution of ∼3.5 billion years. Cyanobacteria contain light-harvesting antennae known as phycobilisomes (PBS) that consist of ∼1500 protein pigments. , PBS is found on the thylakoid membrane in red algae cyanobacteria. , The unique properties of PBS have some advantages in light harvesting, e.g., broadband absorption, fast and efficient energy transfer, angular robustness, and amplification of light concentration . The structural organization of PBS can be classified into several categories such as hemidiscoidal, hemiellipsoidal, bundle-shaped, and block-shaped. , One of the species of cyanobacteria Synechocystis sp.…”
Section: Introductionmentioning
confidence: 99%